Olympic education as a component of professional training of university students - Nadezhda Sergeevna Leontyeva; Lyubov Sergeevna Leontyeva; Maria Vadimovna Koreneva; Maya Victorovna Makhinova (Вестник Майкопского государственного технологического университета, 2023)
The modern paradigm of an educational process at a university, implementation of educational standards of a new generation, that envisages a competence-based approach to training, as well as the realities in the field of international sports and Olympic movement, dictate the obvious need to revise and adjust the disciplines and special courses in order to shape relevant general cultural and professional competencies of students. This circumstance has led to the formulation of the research problem, which consists in eliminating the contradictions dictated, on the one hand, by the need to solve important strategic tasks to optimize vocational education and expand the range of empirical knowledge, on the other hand, by the lack of a necessary set of disciplines in the conditions of reduction classroom hours in favor of independent work of students. In this regard, the purpose of the research was to expand the structure and themes of elective courses, including the content, on the most topical issues and problems of modern international sports and Olympic movement, designed to solve not only the primary tasks of implementation of Olympic education, but also to form a number of FSES HE competencies. The following methods were used in the research: collection, analysis and systematization of primary sources, comparison and contrast, mental experiment, inductive and deductive methods. Key conclusions: tables were developed for the subject visualization reflecting the structure and content of disciplines of choice of historical and sports subjects, their interrelation and interdependence, the discipline of “Olympic education” among them, implemented in the framework of general educational programs in universities.